2013
DOI: 10.1051/epjconf/20134501035
|View full text |Cite
|
Sign up to set email alerts
|

Flow control behind a circular cylinder via a porous cylinder in deep water

Abstract: Abstract. In this present work, the effects of surrounding outer porous cylinder on vortex structure downstream of a circular inner cylinder are investigated experimentally in deep water flow. The porosity of outer cylinder were selected as β = 0. 4, 0.5, 0.6, 0.65, 0.7, 0.75, 0.8 and 0.85. Porosity is defined as the ratio of the gap area on the body to the whole body surface area. The ratio of outer cylinder diameter to inner cylinder diameter, D o /D i was selected as 2.0, i.e. the inner cylinder diameter is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This resulted in an approximate relative error e a =| ( f 1 − f 2 )/( f 1 ) |= 3.98% and a fine-grid convergence in-dex GCI f ine = (1.25e a )/(r p − 1) = 1.36%. The apparent order p is defined according to Equation (13), where q(p) = 0 in this case as r is constant, 32…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in an approximate relative error e a =| ( f 1 − f 2 )/( f 1 ) |= 3.98% and a fine-grid convergence in-dex GCI f ine = (1.25e a )/(r p − 1) = 1.36%. The apparent order p is defined according to Equation (13), where q(p) = 0 in this case as r is constant, 32…”
Section: Methodsmentioning
confidence: 99%
“…There is good agreement on the impact of a full porous coating on the wake of a cylinder, with the wake being stabilised due to the reduction or the delay of vortex shedding [2,[9][10][11][12][13][14][15][16][17][18][19]. Consequently, many studies concluded that the porous coating reduced the fluctuation of aerodynamic forces [2,9,10,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Gozemen [21] suppressed vortex shedding from a circular cylinder by using a porous coating in deep water, showing that the turbulent intensity of the flow downstream the porous cylinder was much smaller than the rigid solid cylinder. Sueki et al [22] cylinder with a diameter of D=25mm.…”
mentioning
confidence: 99%
“…This technique was recently used successfully by [13] who studied experimentally the effects of surrounding outer porous cylinder on vortex structure downstream of a circular inner cylinder in deep water flow. Furthermore, PIV experiments were conducted by [14] and also included in the recent research by [15].…”
Section: Measurement Techniquementioning
confidence: 99%